An ounce of prevention: A pre-randomization protocol to improve retention in substance use disorder clinical trials. (January 2017) - Northrup, Thomas F.; Greer, Tracy L.; Walker, Robrina; Rethorst, Chad D.; Warden, Diane; Stotts, Angela L.; Trivedi, Madhukar H.
Abstract: Background: Missing data in substance use disorder (SUD) research pose a significant threat to internal validity. Participants terminate involvement or become less likely to attend intervention and research visits for many reasons, which should be addressed prior to becoming problematic. During a 9-month study targeting stimulant abuse, early dropouts and participant reported attendance barriers led to implementing a structured, pre-randomization protocol with participants about retention and solution-focused strategies (the "Fireside Chat"). Our aim is to outline this approach and present data on intervention participation and research visit attendance after implementation. Methods/design: STimulant Reduction using Dosed Exercise (STRIDE) was a two-arm, multisite randomized clinical trial testing treatment-as-usual for stimulant abuse/dependence augmented by Exercise or Health Education. For both groups, study intervention visits at the site were scheduled 3/week for 12 weeks followed by 1/week for 24 weeks. During The Chat, research staff thoroughly reviewed participants' expectations, and barriers and solutions to retention. Fifteen participants were randomized (to Exercise or Health Education) prior to and fourteen were randomized after Chat implementation. Intervention and monthly follow-up attendance (before and after implementation) were compared at the site (N = 29) that developed and rigorously implemented The Chat. Results: Individuals who participated in The Chat (n = 14) attended significantly more intervention visits during weeks 1–12 ( p  < 0.001) and weeks 13–36 ( p  < 0.05) and attended more research visits ( p  < 0.001). Discussion: Proactive discussion of expectations and barriers prior to randomization was associated with greater study attendance. SUD researchers should consider tailoring this approach to suit their needs. Further investigation is warranted. Highlights: Missing data are a problem for valid inference in all areas of research. Substance use disorder researchers routinely report over 20% missing data points. Before randomization, a thorough real-world discussion of all potential retention threats may improve attendance/adherence. Adherence and complete data points were each over 90% following implementation of a pre-randomization retention protocol.